EKSTRADISI MENG WANZHOU DALAM PERSPEKTIF HUKUM INTERNASIONAL - Teddy Nurcahyawan; Stevanus Rivaldo (Faculty of Law - Tarumanagara University, 2019)
Extradition is one of the international law field of studies. One of that controversy is Meng Wanzhou’s case, chief financial officer of Huawei. She is known as the daughter of Huawei’s founder Ren Zhengfei and holding Chinese citizenship. Meng Wanzhou was captured and detained by Canadian authority by the request of United States of America when she transitted Canada at Vancouver Airport December 2018. She was charged of frauding which is related to Skycom, a technology company based in Iran. This event led the diplomatic ralation between China, Canada and United States excalated. China government had already released an official statement which expressed anger and their objection about the charged and detention. On the other side, Canada and United States insisted in this event genuinely only a legal matter. This research conducted by a normative and IRAC methods for the analysis part. Based on the research, the request of extradition by United States was consistent with international law principle. Every objection matter by any Party of this case should be done by every diplomatic channels. This thing should be done to maintain the world’s peace.